Occupational closure and wages in Norway. (May 2017) - Bol, Thijs; Drange, Ida
Recent literature has pointed to occupational closure in order to explain wage inequality between occupations. The basic argument of occupational closure is that average occupational wages are higher in closed occupations because these occupations are better able to establish and maintain institutional barriers to access. In this study we analyse occupational closure and its wage effects in Norway by matching newly gathered occupational data on four different closure institutions (licensure, certifications, unionization, and educational credentials) to register data. The results show strong wage effects of licensure and unionization, net of occupational skill requirements. Our analyses furthermore show substantial differences in the returns to occupational closure across social classes: licensure is especially beneficial for higher classes, whereas unionization generates rents for lower classes, implying that occupational closure affects social inequality in Norway.